2004
DOI: 10.1111/j.1600-0447.2004.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the onset of major depression in subjects with subthreshold depression in primary care: a prospective study

Abstract: Objective:  That subjects with subthreshold depression have an increased probability of developing major depression has been confirmed by many studies. However, the factors which may predict the onset of major depression have yet to be fully examined.Method:  We examined the control group of a randomized trial in primary care patients with subthreshold depression (N = 109), of whom 20 had developed major depression 1 year later. Using the vulnerability‐stress theory, we examined which factors predicted the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 28 publications
4
50
1
2
Order By: Relevance
“…The maximum possible pain score was five (severe pain resulting in sleep difficulties) and the minimum was one (no pain). Depression during the previous week was quantified with use of the validated Dutch form of the Center for Epidemiologic Studies-Depression scale (CES-D) 26 . Scores range between zero and sixty points, with a higher score indicating a higher level of depression 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum possible pain score was five (severe pain resulting in sleep difficulties) and the minimum was one (no pain). Depression during the previous week was quantified with use of the validated Dutch form of the Center for Epidemiologic Studies-Depression scale (CES-D) 26 . Scores range between zero and sixty points, with a higher score indicating a higher level of depression 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Depression during the previous week was quantified with use of the validated Dutch form of the Center for Epidemiologic Studies-Depression scale (CES-D) 26 . Scores range between zero and sixty points, with a higher score indicating a higher level of depression 26 . A mean CES-D of 13 was measured in a healthy Dutch population (scores above 16 indicate a depressive disorder) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence that the number of depressive symptoms is related to the onset of major depression (Crum et al, 1994). In a recent study, more general risk factors for getting major depression among subjects with subthreshold depression were examined, such as family history of depression, life events, personality characteristics, and chronic illness (Cuijpers et al, 2004b). It was found that family history and chronic physical illness best predicted the onset of major depression.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, after the intervention, the risk of depression was reduced to 18% post-intervention, which was maintained until the last follow-up conducted. These findings are of great relevance, given that it means reducing the risk of new cases of depression in the future (Cuijpers, Smit, & Willemse, 2005), and exceed the results of the face-to-face format, where the percentage of caregivers at risk of developing depression at post-intervention was 29.5% (Vázquez et al, 2014).…”
Section: Extended Summarymentioning
confidence: 99%